Activation dynamics of ubiquitin-specific protease 7 - Gabrielle J. Valles; Emilie J. Korchak; Dane H. Geddes-Buehre; Nancy Jaiswal; Dmitry M. Korzhnev; Irina Bezsonova (Proceedings of the National Academy of Sciences, 2025)
Ubiquitin-specific protease 7 (USP7) is a deubiquitinating enzyme that plays a crucial role in cellular processes, including the maintenance of genome stability and regulation of antiviral and immune responses. Its dysfunction is linked to various cancers and neurodevelopmental disorders such as Hao-Fountain syndrome. Unlike other USP-family enzymes, the triad of catalytic residues in USP7 adopts an inactive conformation and undergoes rearrangement into the active state upon substrate binding. Despite its potential importance for regulating the enzyme’s activity, the dynamics of USP7 have not been explored. In this study, we combine advanced CPMG NMR relaxation dispersion measurements with the analysis of enzyme kinetics to investigate the conformational dynamics of USP7 in solution and its role in enzyme activation. Our results suggest that apo-USP7 exists in a dynamic equilibrium, transiently switching between inactive and low-populated active conformations, indicating that enzyme activation can occur spontaneously, even in the absence of a substrate. Furthermore, we show that the Hao-Fountain syndrome-associated variant G392D enhances the conformational dynamics of the enzyme, leading to a significant increase in its catalytic activity. This study captures the sparsely populated, "invisible" active conformation of USP7 and demonstrates how changes in enzyme dynamics can contribute to activity, offering broader insights into enzyme function and disease mechanisms.